Green synthesis of Co3O4 nanoparticles using aqueous Avocado (Persea americana) fruit peel extract for multifunctional applications - Vele, Shimona; Ravikumar, C. R.; Kumar, T. Naveen; Timi, David; Chan, K. Y.; Tan, K. B.; T. M., Sharanakumar; Murthy, H. C. Ananda (John Wiley and Sons, 2025)
In the present study, the novel green synthesis approach was employed for the synthesis of Co3O4 nanoparticles (NPs) using an aqueous avocado (Persea americana) fruit peel extract. The synthesized nanomaterial was confirmed by several spectral analytical methods. The x-ray diffraction (XRD) pattern shows an average particle size of 26.29 nm, and the diffraction results match the standard database values for JCPDS No. 073–1701. The SEM micrographs confirmed the presence of NPs with fine, flower-like morphologies which aggregated as clusters. The EDAX spectra confirm the presence of Co and O in the percentages of 46.91% and 53.09%, respectively, which is close to the theoretical ratio (3:4) for Co3O4. The TEM images revealed an enlargement of diffraction rings composed of several diffraction spots, indicating the polycrystalline nature of Co3O4. The NPs’ average size was found to be approximately 87 nm. The energy band gap value of Co3O4 NPs is 1.64 eV. The Fast Orange dye's photodegradation rate was found to be 79% in the presence of Co3O4 NPs under ultraviolet (UV) light irradiation. The highest recorded zones of inhibition for calcined Co3O4 NPs against Bacillus cereus and Escherichia coli were 16.8 and 15.9 mm, respectively. The prepared NPs also exhibited excellent sensitivity towards alcohol detection using cyclic voltammetry with the 0.1 N HCl as a electrolyte. The charge transfer mechanism in Co3O4 NPs is extremely effective, permitting a rapid and efficient energy transfer, according to electrochemical sensing tests. All these results show that the synthesized nanomaterial serves multifunctional applications as photocatalyst, sensor, and antibacterial agent.